Self-lubricating bearing and method for its production and use
Patent Information
- Application Number
- CN202511714506.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-20
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-11-20
AI Technical Summary
[0005]因此,本发明要解决的技术问题在于同时克服现有注塑PEEK轴承存在的延展性不足、界面结合强度低、反卷易开裂的缺陷,从而提供解决上述问题的一种自润滑轴承及其制备方法和应用
1.本发明通过梯度铜粉孔隙结构、晶须增韧PEEK膜设计及特定工艺控制的协同作用,成功制备了高性能自润滑轴承。具体地,中位粒径比≥7.5:1、孔隙率差≥25%的梯度铜粉结构,结合特定的热压工艺,使界面剪切强度提升至33~42MPa;材料在保持75~96MPa高拉伸强度的同时,断裂伸长率达到了24%~35%;优化的反卷成型工艺彻底解决了开裂问题,合格率达100%。性能测试表明,本发明轴承的磨损率低至2~5.0×10-7mm3/(N·m),摩擦系数在0.11~0.17之间,综合性能显著优于传统注塑PEEK轴承。
Smart Images

Figure CN121339446B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sliding bearing technology, specifically to a self-lubricating bearing, its preparation method, and its application. Background Technology
[0002] Wind turbine gearbox sliding bearings have long faced the challenges of harsh operating conditions such as low-speed heavy loads and frequent start-stop cycles. While traditional Babbitt metal bearings possess good wear resistance, their reliance on forced lubrication systems presents significant technical limitations due to the difficulty of maintenance in the high-altitude environment at the top of the tower. On one hand, sudden changes in wind speed can easily lead to momentary oil cut-off, causing metal-on-metal bonding failure; on the other hand, stress relaxation caused by the interference fit between the bearing and the shaft can easily lead to fatigue detachment. To address the problem of bearing fatigue detachment, the industry has introduced laser cladding of copper alloy layers. This technology forms a strong metallurgical interface by fusing a copper alloy layer onto the bearing substrate surface, fundamentally enhancing the bearing's adhesion strength and effectively suppressing fatigue detachment. However, this technology still suffers from metal-on-metal bonding failure under lean / cut-off oil conditions. Therefore, an additional polymer self-lubricating coating is required. Although this coating solves the lubrication dependence problem, it is limited by the maximum coating thickness (usually no more than 0.8 mm), making it difficult to compensate for deformation under eccentric loads, severely impacting bearing life. In summary, existing technical solutions based on forced lubrication or thin-layer self-lubricating coatings are insufficient to meet the requirements of long-term reliable operation of wind turbine gearbox bearings under maintenance-free conditions.
[0003] In recent years, injection-molded polyetheretherketone (PEEK) bearing technology has been applied in the wind power field as a novel solution. Its typical structure is a three-layer composite: a steel backing substrate, a copper powder transition layer of the same particle size, and an injection-molded PEEK layer. This technology is mainly used in wind turbine main shaft bearings, and its manufacturing process involves directly molding PEEK material onto the bearing substrate via injection molding. This method improves the self-lubricating performance of the bearing to some extent. However, this technology has the following limitations: First, the injection molding process leads to excessively high PEEK crystallinity and insufficient material ductility; second, the interfacial bonding strength of the homogeneous copper powder layer is limited, making it prone to cracking defects during reverse rolling, which makes it difficult to meet the design requirement of a 20-year ultra-long lifespan for wind turbine bearings.
[0004] To overcome these shortcomings, researchers have attempted to improve bearing performance by adding whisker reinforcement phases or using gradient copper powder structures. However, these improvement solutions often focus only on optimizing a single performance indicator. For example, whisker reinforcement technology mainly focuses on improving simple wear resistance, while gradient copper powder design mainly targets the improvement of the load-bearing capacity of thin-layer materials. Neither has effectively addressed the comprehensive performance requirements of PEEK materials in wind power applications, resulting in existing injection-molded PEEK bearings still facing problems such as insufficient ductility, low interfacial bonding strength, and easy cracking due to anti-rolling. Summary of the Invention
[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defects of existing injection-molded PEEK bearings, such as insufficient ductility, low interfacial bonding strength, and easy cracking due to reverse rolling, thereby providing a self-lubricating bearing, its preparation method and application, which solve the above problems.
[0006] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a method for preparing a self-lubricating bearing, comprising: Preparation of a gradient copper powder layer: A dense copper powder transition layer and a porous copper powder buffer layer are deposited and sintered on a substrate support layer, wherein the dense copper powder transition layer is directly bonded to the substrate support layer, and the porous copper powder buffer layer is superimposed on the dense copper powder transition layer; wherein the ratio of the median particle size of the copper powder used in the porous copper powder buffer layer to that used in the dense copper powder transition layer is ≥7.5:1; the porosity P2 of the porous copper powder buffer layer is similar to that of the dense copper powder transition layer. The porosity difference P1 satisfies P2-P1≥25%; the porous copper powder buffer layer forms interconnected pores with a diameter of 200~500μm; in the step of preparing the gradient copper powder layer, by controlling the ratio of the median particle size of the copper powder used in the porous copper powder buffer layer to that used in the dense copper powder transition layer to be ≥7.5:1, the synergistic effect of the double-layer structure is achieved: the lower dense structure ensures a firm bond with the substrate support layer, and the upper loose structure provides channels for PEEK melt penetration. By limiting the porosity difference P2 of the porous copper powder buffer layer to P2-P1≥25%, sufficient pore space in the upper layer is ensured. If the porosity difference is insufficient, insufficient PEEK melt penetration will result in insufficient penetration into the copper powder layer. By limiting the interconnected pores formed by the porous copper powder buffer layer to 200~500μm, effective flow of PEEK melt is ensured. If the aperture is less than 200μm, the flow rate at the front of the PEEK melt will be too slow, which will affect the efficiency of industrial production; while if the aperture is greater than 500μm, it may weaken the mechanical support strength of the copper powder layer.
[0007] Preparation of toughened PEEK film: A mixture containing PEEK resin, whiskers, solid lubricant, and flow modifier is thermoplasticized into a film. The cooling rate during thermoplasticizing is 20~80℃ / s. By controlling the cooling rate within this range, the crystallinity of PEEK is precisely controlled between 20% and 25%. When the cooling rate is below 20℃ / s, excessively high crystallinity (>25%) leads to a decrease in material ductility; when the cooling rate is above 80℃ / s, the molecular chains are rapidly frozen, resulting in insufficient crystallization, and excessively low crystallinity (<20%) affects the material's wear resistance and dimensional stability. This crystallinity range ensures that the PEEK film simultaneously possesses the necessary flexibility for reverse rolling and the wear resistance required for bearing applications. Composite processing: The toughened PEEK film and the gradient copper powder layer are hot-pressed together to obtain a composite material containing a toughened PEEK sliding layer, a gradient copper powder layer and a substrate support layer from top to bottom. Reverse rolling forming: The composite sheet is heated to 150~170℃ for plastic bending and a back pressure of 0.5~2MPa is applied. Finally, it is rolled and welded to form a self-lubricating bearing. The heating temperature is controlled within the plastic deformation window of 10~20℃ above the glass transition temperature (Tg) of the PEEK material, allowing the material to enter a highly elastic / viscoelastic state for optimal formability. The back pressure is applied simultaneously to the outer bending surface of the sheet through a curved hot press plate to suppress potential instability and wrinkling of the PEEK layer during bending, as well as the springback effect of the whisker reinforcement phase, preventing interlayer separation caused by bending stress. A back pressure below 0.5MPa is insufficient to effectively constrain material deformation, while a pressure above 2MPa may lead to whisker fracture or excessive flow and compression of the PEEK matrix, affecting the final properties of the material.
[0008] In one optional embodiment, the median particle size of the copper powder used in the dense copper powder transition layer is 15~25μm; this particle size range can ensure that the copper powder achieves sufficient diffusion and flow during sintering to form a dense structure. And / or, the porosity P1 of the dense copper powder transition layer is 10~16%; this porosity range can ensure an effective metallurgical bond with the substrate support layer and provide a stable support foundation for the upper porous structure. And / or, the median particle size of the copper powder used in the porous copper powder buffer layer is 130~170μm; this coarse particle size characteristic is conducive to the formation of a through-pore network; And / or, the porosity P2 of the porous copper powder buffer layer is 40~45%; this high porosity structure provides sufficient channel space for PEEK melt penetration, ensuring a penetration depth of ≥60%; And / or, the copper powder used for laying the dense copper powder transition layer and the porous copper powder buffer layer includes copper-tin alloy powder (e.g., CuSn10, CuSn13) and / or copper-tin-zinc alloy powder (e.g., CuSn8Zn3), preferably, the copper-tin alloy powder is CuSn10 bronze powder. Using copper-tin alloy powder enables the formation of a denser copper-iron diffusion layer with the steel substrate during sintering. Simultaneously, its solidus temperature is lower than that of pure copper, which is beneficial for achieving sufficient atomic diffusion and metallurgical bonding at a relatively low sintering temperature, thereby improving the interfacial bonding strength.
[0009] In one optional embodiment, the sintering process of the dense copper powder transition layer includes: heating to 850°C~900°C at a heating rate of 3~6°C / min under vacuum, and holding at that temperature for 30~90min for high-temperature sintering. This process aims to achieve high densification of the transition layer and form a metallurgically bonded interface diffusion layer with the substrate support layer, thereby achieving high-strength interface bonding; And / or, the sintering process of the porous copper powder buffer layer includes: heating to 680℃~720℃ at a heating rate of 3~6℃ / min in a vacuum environment, holding for 20~60min for low-temperature pre-sintering, then heating to 850℃~900℃ at a heating rate of not less than 10℃ / min, holding for 5~20min for rapid sintering, and then rapidly cooling at a cooling rate of not less than 50℃ / s; by controlling the stepped heating rate and rapid cooling, the necessary bonding strength between particles is achieved while suppressing excessive particle growth, thereby maintaining a high porosity structure of 40%~45%; And / or, the substrate support layer comprises a low-carbon steel substrate. For example, a low-carbon steel substrate with a carbon content of 0.05~0.25%. Using a low-carbon steel substrate enables the formation of a stable iron-copper diffusion metallurgical bond with the copper powder layer during high-temperature sintering. Simultaneously, its low carbon content ensures sufficient structural strength of the support layer while avoiding the risk of hardened structures and brittle interfacial phases generated during rapid cooling of high-carbon steel, thereby ensuring the overall strength and toughness of the bearing structure.
[0010] In one alternative embodiment, in the step of preparing the toughened PEEK film, the mixture contains 53-82 wt% PEEK resin, 10-25 wt% whiskers, 3-10 wt% solid lubricant and 5-12 wt% flow modifier, based on a mass of 100 wt%. Optionally, the mixture contains 63-82 wt% PEEK resin, 10-20 wt% whiskers, 3-7 wt% solid lubricant, and 5-10 wt% flow modifier. In this preferred formulation, PEEK resin serves as the continuous phase, providing matrix properties; 10-20 wt% whiskers form a reinforcing network; below 10 wt% the toughening effect is insufficient, while above 20 wt% it significantly reduces melt flowability; 3-7 wt% solid lubricant enhances the overall hardness of the material and constructs a wear-resistant skeleton through its high hardness characteristics, while simultaneously forming a lubrication transfer film at the contact interface during friction, achieving friction reduction and wear resistance; 5-10 wt% flow modifier ensures processing flowability under high-filling systems. The components work synergistically within the above ranges to achieve a multi-level structural design of "rigid-hard-slippery": whiskers primarily contribute "rigidity," solid lubricant undertakes the function of a "hard" wear-resistant skeleton and synergistically achieves a "slippery" friction-reducing effect, and flow modifier ensures molding processability. And / or, the temperature for thermoplastic film formation is 375℃~395℃, preferably 385℃; this temperature range is about 30~50℃ above the PEEK melting temperature (Tm≈343℃), which can ensure sufficient melting and plasticization while avoiding high-temperature degradation; And / or, the thermoplastic film formation method includes casting film formation and / or calendering film formation; wherein, the casting film formation process induces the whiskers to align along the flow direction through the shear flow field in the die head, while the calendering film formation process achieves whisker orientation through the stretching flow field and stretching effect between the roll gaps; And / or, the PEEK crystallinity in the toughened PEEK film is 20%~25%. This crystallinity range is achieved by controlling the cooling rate of 20~80℃ / s, which is key to balancing the toughness and wear resistance of the material.
[0011] In one optional embodiment, the hot-pressing composite process includes: covering a toughened PEEK film onto a gradient copper powder layer to form a composite system and then performing a hot-pressing process. The hot pressing process includes the following steps: a) Stepwise heating: First, heat the composite system from room temperature to 280-320℃ at a heating rate of 3-6℃ / min, hold for 5-15min for preheating and temperature equalization, and then continue heating to 380-400℃ at a heating rate of 3-6℃ / min to fully melt the toughened PEEK film. b) Segmented pressurization: During the melting stage, under vacuum conditions, a pressure of 3-6 MPa is first applied and maintained for 3-8 min; then the pressure is increased to 12-18 MPa and maintained for 20-30 min. The hot-pressing composite process adopts a stepped heating (3-6℃ / min) and segmented pressurization strategy: in the initial low temperature stage (280-320℃), preheating is used to reduce thermal stress. After reaching the PEEK viscous flow temperature (380-400℃), the melt is first initially wetted on the surface of copper powder with a low pressure of 3-6 MPa (3-8 min), and then driven to penetrate the porous layer depth with a high pressure of 12-18 MPa (20-30 min), ultimately achieving a penetration depth ≥60% of the total copper layer thickness.
[0012] In one optional embodiment, the whiskers include at least one of potassium titanate whiskers, calcium sulfate whiskers, and silicon carbide whiskers, preferably potassium titanate whiskers; wherein potassium titanate whiskers, with their high strength and unique needle-like structure, can form an efficient stress transfer network in the PEEK matrix. And / or, the aspect ratio of the whiskers is >10, preferably 15~30; its high aspect ratio is beneficial for stress transfer and toughening. And / or, the solid lubricant includes at least one of zirconium phosphate, molybdenum disulfide, and graphite, preferably zirconium phosphate; wherein zirconium phosphate, with its layered crystal structure and moderate hardness, can reduce the coefficient of friction through micro-slippage and also serve as a wear-resistant skeleton to improve the wear resistance of the material. And / or, the flow modifier includes at least one of polytetrafluoroethylene (PTFE) micropowder, polyethylene wax, and stearate, preferably polytetrafluoroethylene micropowder. It effectively reduces the frictional resistance of each component by forming a lubricating interface in the resin melt, ensuring that the highly filled system maintains excellent processing flowability during thermoplastic molding.
[0013] In one optional embodiment, the rolling welding method is high-frequency induction welding. Preferably, the process parameters for high-frequency induction welding are: welding temperature of 970~990℃ and welding time of 8~12s. This process achieves instantaneous localized heating by precisely concentrating energy on the weld area, ensuring metallurgical bonding of the steel backing substrate while avoiding overheating that could damage the performance of the adjacent PEEK layer, thereby ensuring the integrity of the overall bearing structure.
[0014] Secondly, the present invention also provides a self-lubricating bearing for a wind turbine gearbox, which is prepared by the above-described method for preparing a self-lubricating bearing.
[0015] In one optional embodiment, the thickness of the substrate support layer is 8-10 mm; this thickness range can provide the bearing with the necessary structural rigidity and support strength to withstand the complex load conditions of the wind turbine gearbox. And / or, the thickness of the dense copper powder transition layer is 0.05~0.1mm; this thin layer design ensures an effective metallurgical bond with the substrate support layer while minimizing the impact on the thermal resistance of the overall bearing structure. And / or, the thickness of the porous copper powder buffer layer is 0.3~0.6mm; this thickness range provides sufficient space channels for PEEK melt penetration, ensuring a penetration depth of ≥60% and forming a robust interlocking structure; And / or, the thickness of the toughened PEEK sliding layer is ≥0.5mm, preferably 1~3mm. This thickness design ensures that the bearing has sufficient self-lubricating material reserves and wear capacity, while avoiding the molding difficulties and internal stress accumulation problems caused by excessive thickness.
[0016] Thirdly, the present invention also provides a wind turbine generator set, wherein the gearbox uses the aforementioned wind turbine gearbox self-lubricating bearing.
[0017] The technical solution of this invention has the following advantages: 1. This invention successfully fabricates high-performance self-lubricating bearings through the synergistic effect of a gradient copper powder porosity structure, a whisker-toughened PEEK film design, and specific process control. Specifically, a gradient copper powder structure with a median particle size ratio ≥7.5:1 and a porosity difference ≥25%, combined with a specific hot-pressing process, increases the interfacial shear strength to 33~42MPa; while maintaining a high tensile strength of 75~96MPa, the elongation at break reaches 24%~35%; the optimized reverse-rolling molding process completely solves the cracking problem, achieving a 100% pass rate. Performance tests show that the wear rate of the bearings of this invention is as low as 2~5.0×10⁻⁶. -7 mm 3 With a coefficient of friction between 0.11 and 0.17, its overall performance is significantly better than that of traditional injection-molded PEEK bearings.
[0018] 2. This invention solves the problem of high flow resistance in micropores of high-viscosity PEEK melt by using a synergistic hot-pressing composite process of "stepped heating and segmented pressurization" combined with a vacuum environment. In this process, the stepped heating strategy (preheating to 380~400℃ after preheating at 280~320℃) effectively eliminates thermal stress between different materials, providing a stable rheological environment for the polymer melt. Compared with processes lacking a preheating step, the interfacial shear strength and penetration depth are significantly improved. The segmented pressurization strategy (low-pressure wetting at 3~6MPa followed by high-pressure penetration at 12~18MPa) precisely matches the seepage dynamics of PEEK melt in micropores, ensuring sufficient surface wetting and gas expulsion before driving the melt to penetrate to a copper layer thickness of ≥60%, thus achieving high-strength interfacial bonding at both the molecular-level wetting and macroscopic structural interlocking levels. Attached Figure Description
[0019] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0020] Figure 1 This is an overall penetration morphology diagram of the PEEK-copper layer interface in the self-lubricating bearing prepared in Embodiment 5 of the present invention; Figure 2 This is a microscopic morphology diagram of PEEK infiltration into the copper layer in the self-lubricating bearing prepared in Example 5 of the present invention. Detailed Implementation
[0021] The following embodiments are provided to better understand the present invention, but the following embodiments do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the scope of protection of the present invention.
[0022] Unless otherwise specified, all experimental steps or conditions in the examples were performed according to conventional experimental procedures and conditions in the art. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0023] Example 1 This embodiment provides a method for preparing a self-lubricating bearing, the specific steps of which are as follows: 1) Preparation of Gradient Copper Powder Layer: An 8mm thick Q235 low-carbon steel plate was selected as the substrate support layer. After sandblasting and acetone cleaning and activation, a layer of CuSn10 bronze powder with a median particle size of 20μm and a thickness of approximately 1.0mm was laid. The powder-coated component was placed in a vacuum sintering furnace. After evacuation, it was heated to 880℃ at a heating rate of 5℃ / min and held for 60 minutes, followed by furnace cooling. After sintering, a dense copper powder transition layer with a metallurgical bond to the steel plate was formed, with a thickness of approximately 0.09mm and a porosity P1 of approximately 16%. A layer of CuSn10 bronze powder with a median particle size of 150μm and a thickness of approximately 1.8mm was then uniformly laid on the sintered dense copper powder transition layer. The component was placed back into the vacuum sintering furnace. After evacuation, the following sintering procedure was performed: First, it was heated to 700℃ at a heating rate of 5℃ / min and held for 30 minutes to complete low-temperature pre-sintering; then, it was rapidly heated to 880℃ at a heating rate of 15℃ / min and held for 10 minutes for final sintering; finally, it was rapidly cooled at a rate of 50℃ / s. After sintering, a porous copper powder buffer layer was formed with a thickness of approximately 0.56 mm, a porosity P2 of approximately 41.24%, and pore sizes mainly distributed between 250 and 400 μm.
[0024] 2) Preparation of toughened PEEK film: 72 wt% PEEK resin (Victrex 450G), 15 wt% potassium titanate whiskers (aspect ratio of 20~30), 5 wt% zirconium phosphate and 8 wt% PTFE micro powder were mixed at high speed and then melt-blended and granulated at 385℃ using a twin-screw extruder. Subsequently, the mixture was calendered at 385℃ using a twin-roll calender to form a film with a thickness of 2.2 mm. The cooling rate was controlled at 50℃ / s to keep the PEEK crystallinity (DSC method (differential scanning calorimetry)) at 22.99%.
[0025] 3) Composite processing: The toughened PEEK film was coated on the porous copper powder buffer layer of the gradient copper powder layer and placed in a vacuum hot press. It was first heated from room temperature to 300°C at a heating rate of 5°C / min and held for 10 minutes for preheating and temperature homogenization. Then, it was heated to 385°C at a heating rate of 5°C / min to fully melt the toughened PEEK film. Subsequently, a pressure of 5MPa was applied and held for 5 minutes, and then the pressure was increased to 15MPa and held for 25 minutes to complete the hot pressing composite. The penetration depth of the PEEK melt was measured to be 65% of the total thickness of the copper layer.
[0026] 4) Reverse rolling: The composite sheet is heated to 150℃, plastically bent in a mold while a back pressure of 1MPa is applied simultaneously, and finally rolled into a circle by high-frequency induction welding at 980℃ / 10s to obtain the self-lubricating bearing. The toughened PEEK sliding layer of the self-lubricating bearing has a thickness of approximately 2.0mm.
[0027] Molding quality verification: Ten bearing samples were continuously prepared using the same process parameters as described above. The PEEK layer and interface area after reverse rolling were inspected by macroscopic observation. No macroscopic cracks, wrinkles, or interlayer separation were observed in any of the ten samples, and the reverse rolling pass rate was 100%.
[0028] Performance Testing: Three samples were randomly selected from those that passed molding quality verification. Performance characterization was performed according to standard test methods, and the results were averaged: PEEK layer tensile strength (test standard ASTM D638) was 92.67 MPa, elongation at break (test standard ASTM D638) was 35%, interfacial shear strength (test standard ASTM D1002) was 42 MPa, dry friction coefficient (test standard ASTM G77-17) was 0.12, and wear rate was 2 × 10⁻⁶. -7 mm 3 / (N·m).
[0029] Example 2 This embodiment provides a method for preparing a self-lubricating bearing, the specific steps of which are as follows: 1) Preparation of Gradient Copper Powder Layer: An 8mm thick Q235 low-carbon steel plate was selected as the substrate support layer. After sandblasting and acetone cleaning and activation, a layer of CuSn10 bronze powder with a median particle size of 15μm and a thickness of approximately 0.9mm was laid. The powder-coated component was placed in a vacuum sintering furnace. After evacuation, it was heated to 850℃ at a heating rate of 3℃ / min and held for 90 minutes, followed by furnace cooling. After sintering, a dense copper powder transition layer with a metallurgical bond to the steel plate was formed, with a thickness of approximately 0.05mm and a porosity P1 of approximately 10%. A layer of CuSn10 bronze powder with a median particle size of 130μm and a thickness of approximately 1.5mm was then uniformly laid on the sintered lower dense copper powder transition layer. The components were placed back into the vacuum sintering furnace. After evacuation, the following sintering procedure was performed: First, the temperature was increased to 680°C at a heating rate of 3°C / min and held for 60 minutes to complete low-temperature pre-sintering; then, the temperature was rapidly increased to 850°C at a heating rate of 10°C / min and held for 20 minutes for final sintering; finally, the temperature was rapidly cooled at a rate of 50°C / s. After sintering, a porous copper powder buffer layer was formed with a thickness of approximately 0.30 mm, a porosity P2 of approximately 40%, and pore sizes mainly distributed between 200 and 240 μm.
[0030] 2) Preparation of toughened PEEK film: 82 wt% PEEK resin (Victrex 450G), 10 wt% potassium titanate whiskers (aspect ratio of 20~30), 3 wt% zirconium phosphate and 5 wt% PTFE micro powder were mixed at high speed and then melt-blended and granulated at 375℃ using a twin-screw extruder. Subsequently, the mixture was calendered at 375℃ using a twin-roll calender to form a film with a thickness of 1.8 mm. The cooling rate was controlled at 20℃ / s to keep the PEEK crystallinity (DSC method) at 25%.
[0031] 3) Composite processing: The toughened PEEK film was coated on the porous copper powder buffer layer of the gradient copper powder layer and placed in a vacuum hot press. It was first heated from room temperature to 280°C at a heating rate of 3°C / min and held for 15 minutes for preheating and temperature homogenization. Then, it was heated to 380°C at a heating rate of 3°C / min to fully melt the toughened PEEK film. Subsequently, a pressure of 3MPa was applied and held for 8 minutes, and then the pressure was increased to 12MPa and held for 30 minutes to complete the hot pressing composite. The penetration depth of the PEEK melt was measured to be 60% of the total thickness of the copper layer.
[0032] 4) Reverse rolling: The composite sheet is heated to 150℃, plastically bent in a mold while a back pressure of 2MPa is applied simultaneously, and finally rolled into a circle by high-frequency induction welding at 970℃ / 12s to obtain the self-lubricating bearing. The toughened PEEK sliding layer of the self-lubricating bearing has a thickness of approximately 1.5mm.
[0033] Molding quality verification: Ten bearing samples were continuously prepared using the same process parameters as described above. The toughened PEEK sliding layer and interface area after reverse rolling were inspected by macroscopic observation. No macroscopic cracks, wrinkles, or interlayer separation were observed in any of the ten samples, and the reverse rolling pass rate was 100%.
[0034] Performance Testing: Three samples were randomly selected from those that passed molding quality verification. Performance characterization was performed according to standard test methods, and the results were averaged: Tensile strength of the toughened PEEK sliding layer (test standard ASTM D638) was 78 MPa, elongation at break (test standard ASTM D638) was 32%, interfacial shear strength (test standard ASTM D1002) was 35 MPa, dry friction coefficient (test standard ASTM G77-17) was 0.15, and wear rate was 4.2 × 10⁻⁶. -7 mm 3 / (N·m).
[0035] Example 3 This embodiment provides a method for preparing a self-lubricating bearing, the specific steps of which are as follows: 1) Preparation of Gradient Copper Powder Layer: An 8mm thick Q235 low-carbon steel plate was selected as the substrate support layer. After sandblasting and acetone cleaning and activation, a layer of CuSn10 bronze powder with a median particle size of 22μm and a thickness of approximately 1.1mm was laid. The powder-coated component was placed in a vacuum sintering furnace. After evacuation, it was heated to 900℃ at a heating rate of 6℃ / min and held for 30 minutes, followed by furnace cooling. After sintering, a dense copper powder transition layer with a metallurgical bond to the steel plate was formed, with a thickness of approximately 0.1mm and a porosity P1 of approximately 16%. A layer of CuSn10 bronze powder with a median particle size of 170μm and a thickness of approximately 2.0mm was uniformly laid on the sintered lower dense copper powder transition layer. The component was placed back into the vacuum sintering furnace. After evacuation, the following sintering procedure was performed: First, it was heated to 720°C at a heating rate of 6°C / min and held for 20 minutes to complete low-temperature pre-sintering; then, it was rapidly heated to 900°C at a heating rate of 20°C / min and held for 5 minutes for final sintering; finally, it was rapidly cooled at a rate of 50°C / s. After sintering, a porous copper powder buffer layer was formed with a thickness of approximately 0.60 mm, a porosity P2 of approximately 45%, and pore sizes mainly distributed between 450 and 500 μm.
[0036] 2) Preparation of toughened PEEK film: 63 wt% PEEK resin (Victrex 450G), 20 wt% potassium titanate whiskers (aspect ratio of 20~30), 7 wt% zirconium phosphate and 10 wt% PTFE micro powder were mixed at high speed and then melt-blended and granulated at 395℃ using a twin-screw extruder. Subsequently, the mixture was calendered at 395℃ using a twin-roll calender to form a film with a thickness of 3.2 mm. The cooling rate was controlled at 80℃ / s to keep the PEEK crystallinity (DSC method) at 20%.
[0037] 3) Composite processing: The toughened PEEK film was coated on the porous copper powder buffer layer of the gradient copper powder layer and placed in a vacuum hot press. It was first heated from room temperature to 320°C at a heating rate of 6°C / min and held for 5 minutes for preheating and temperature homogenization. Then, it was heated to 400°C at a heating rate of 6°C / min to fully melt the toughened PEEK film. Subsequently, a pressure of 6MPa was applied and held for 3 minutes, and then the pressure was increased to 18MPa and held for 20 minutes to complete the hot pressing composite. The penetration depth of the PEEK melt was measured to be 70% of the total thickness of the copper layer.
[0038] 4) Reverse rolling: The composite sheet is heated to 170℃, plastically bent in a mold while a back pressure of 0.5MPa is applied simultaneously, and finally rolled into a circle by high-frequency induction welding at 990℃ / 8s to obtain the self-lubricating bearing. The toughened PEEK sliding layer of the self-lubricating bearing has a thickness of approximately 3.0mm.
[0039] Molding quality verification: Ten bearing samples were continuously prepared using the same process parameters as described above. The toughened PEEK sliding layer and interface area after reverse rolling were inspected by macroscopic observation. No macroscopic cracks, wrinkles, or interlayer separation were observed in any of the ten samples, and the reverse rolling pass rate was 100%.
[0040] Performance Testing: Three samples were randomly selected from those that passed molding quality verification. Performance characterization was performed according to standard test methods, and the results were averaged: Tensile strength of the toughened PEEK sliding layer (test standard ASTM D638) was 88 MPa, elongation at break (test standard ASTM D638) was 30%, interfacial shear strength (test standard ASTM D1002) was 35 MPa, dry friction coefficient (test standard ASTM G77-17) was 0.16, and wear rate was 3.5 × 10⁻⁶. -7 mm 3 / (N·m).
[0041] Example 4 This embodiment provides a method for preparing a self-lubricating bearing. The only difference between this method and Embodiment 1 is that the preheating and homogenization steps are omitted in step 3). Specifically, the toughened PEEK film is coated on a porous copper powder buffer layer of a gradient copper powder layer and placed in a vacuum hot press. The film is heated directly from room temperature to 385°C at a heating rate of 5°C / min to melt the toughened PEEK film. Then, a pressure of 5MPa is applied and held for 5 minutes, and then the pressure is increased to 15MPa and held for 25 minutes to complete the hot pressing composite. The penetration depth of the PEEK melt is measured to be 58% of the total thickness of the copper layer.
[0042] Molding quality verification: Ten bearing samples were continuously prepared using the same process parameters as described above. The toughened PEEK sliding layer and interface area after reverse rolling were inspected by macroscopic observation. No macroscopic cracks, wrinkles, or interlayer separation were observed in any of the ten samples, and the reverse rolling pass rate was 100%.
[0043] Performance Testing: Three samples were randomly selected from those that passed molding quality verification. Performance characterization was performed according to standard test methods, and the results were averaged: Tensile strength of the toughened PEEK sliding layer (test standard ASTM D638) was 90 MPa, elongation at break (test standard ASTM D638) was 31%, interfacial shear strength (test standard ASTM D1002) was 35 MPa, dry friction coefficient (test standard ASTM G77-17) was 0.13, and wear rate was 3.8 × 10⁻⁶. -7 mm 3 / (N·m).
[0044] Example 5 This embodiment provides a method for preparing a self-lubricating bearing, the specific steps of which are as follows: 1) Preparation of Gradient Copper Powder Layer: An 8mm thick Q235 low-carbon steel plate was selected as the substrate support layer. After sandblasting and acetone cleaning and activation, a layer of CuSn10 bronze powder with a median particle size of 18μm and a thickness of approximately 0.95mm was laid. The powder-coated component was placed in a vacuum sintering furnace. After evacuation, it was heated to 870℃ at a heating rate of 4℃ / min and held for 45 minutes, followed by furnace cooling. After sintering, a dense copper powder transition layer with a metallurgical bond to the steel plate was formed, with a thickness of approximately 0.076mm and a porosity P1 of approximately 14%. A layer of CuSn10 bronze powder with a median particle size of 160μm and a thickness of approximately 1.9mm was then uniformly laid on the sintered dense copper powder transition layer. The components were placed back into the vacuum sintering furnace. After evacuation, the following sintering procedure was performed: First, the temperature was increased to 710°C at a heating rate of 4°C / min and held for 40 minutes to complete low-temperature pre-sintering; then, the temperature was rapidly increased to 870°C at a heating rate of 15°C / min and held for 15 minutes for final sintering; finally, the temperature was rapidly cooled at a rate of 50°C / s. After sintering, a porous copper powder buffer layer was formed with a thickness of approximately 0.485 mm, a porosity P2 of approximately 43%, and pore sizes mainly distributed between 300 and 450 μm.
[0045] 2) Preparation of toughened PEEK film: 70 wt% PEEK resin (Victrex 450G), 16 wt% potassium titanate whiskers (aspect ratio of 20~30), 6 wt% zirconium phosphate and 8 wt% PTFE micro powder were mixed at high speed and then melt-blended and granulated at 390℃ using a twin-screw extruder. Subsequently, the mixture was calendered at 390℃ using a twin-roll calender to form a film with a thickness of 1.5 mm. The cooling rate was controlled at 60℃ / s to keep the PEEK crystallinity (DSC method) at 23%.
[0046] 3) Composite processing: The toughened PEEK film was coated on the porous copper powder buffer layer of the gradient copper powder layer and placed in a vacuum hot press. First, it was heated from room temperature to 310°C at a heating rate of 4°C / min and held for 8 minutes for preheating and temperature homogenization. Then, it was heated to 390°C at a heating rate of 4°C / min to fully melt the toughened PEEK film. Then, a pressure of 4MPa was applied and held for 6 minutes, and then the pressure was increased to 16MPa and held for 25 minutes to complete the hot pressing composite. The penetration depth of the PEEK melt was measured to be 71% of the total thickness of the copper layer.
[0047] 4) Reverse Rolling Forming: The composite sheet is heated to 160℃, plastically bent in a mold while a back pressure of 1.5MPa is applied simultaneously, and finally rolled into a circle by high-frequency induction welding at 980℃ / 10s to obtain the self-lubricating bearing. The toughened PEEK sliding layer of the self-lubricating bearing has a thickness of approximately 0.767mm. The total thickness of the sliding layer plus the PEEK penetrating into the copper powder layer is approximately 1.112mm.
[0048] The self-lubricating bearing sample prepared in this embodiment was subjected to cross-sectional dissection, and the penetration of PEEK in the gradient copper powder layer was observed by electron microscopy. The results are as follows: Figure 1 and Figure 2 As shown. Figure 1 The overall penetration morphology of the PEEK-copper interface is shown, revealing a continuous and tightly bonded interface between the PEEK layer and the copper layer. Figure 2 The microstructure of PEEK penetration into the copper layer is shown, and the excellent filling effect of PEEK melt on the pores between copper powder particles can be clearly observed.
[0049] Molding quality verification: Ten bearing samples were continuously prepared using the same process parameters as described above. The toughened PEEK sliding layer and interface area after reverse rolling were inspected by macroscopic observation. No macroscopic cracks, wrinkles, or interlayer separation were observed in any of the ten samples, and the reverse rolling pass rate was 100%.
[0050] Performance Testing: Three samples were randomly selected from those that passed molding quality verification. Performance characterization was performed according to standard test methods, and the results were averaged: Tensile strength of the toughened PEEK sliding layer (test standard ASTM D638) was 89 MPa, elongation at break (test standard ASTM D638) was 33%, interfacial shear strength (test standard ASTM D1002) was 40 MPa, dry friction coefficient (test standard ASTM G77-17) was 0.11, and wear rate was 2.2 × 10⁻⁶. -7 mm 3 / (N·m).
[0051] Example 6 This embodiment provides a method for preparing a self-lubricating bearing. The only difference between this method and Embodiment 1 is that in step 2), when preparing the toughened PEEK film, the mass percentage of the whiskers is adjusted from 15wt% to 25wt%. In order to keep the mass of the mixture for preparing the toughened PEEK film unchanged, the amount of PEEK resin is reduced accordingly. That is, the composition of the mixture is: 62wt% PEEK resin, 25wt% potassium titanate whiskers, 5wt% zirconium phosphate and 8wt% PTFE micro powder.
[0052] Molding quality verification: Ten bearing samples were continuously prepared using the same process parameters as described above. The toughened PEEK sliding layer and interface area after reverse rolling were inspected by macroscopic observation. No macroscopic cracks, wrinkles, or interlayer separation were observed in any of the ten samples, and the reverse rolling pass rate was 100%.
[0053] Performance test results: The toughened PEEK sliding layer has a tensile strength of 96 MPa, an elongation at break of 24%, an interfacial shear strength of 33 MPa, a dry friction coefficient of 0.17, and a wear rate of 4.5 × 10⁻⁶. -7 mm3 / (N·m). Based on the test results, it is inferred that the excessive proportion of potassium titanate whiskers leads to a decrease in its dispersion in the matrix, resulting in stress concentration. Although the tensile strength is slightly improved, the brittleness of the material is significantly increased (the elongation at break decreases), and the interfacial bonding strength is severely damaged (the interfacial shear strength decreases). At the same time, the friction coefficient increases because the whiskers are easy to fall off during the friction process.
[0054] Example 7 This embodiment provides a method for preparing a self-lubricating bearing. The only difference between this method and Embodiment 1 is that in step 2), when preparing the toughened PEEK film, the mass percentage of zirconium phosphate is adjusted from 5 wt% to 10 wt%. In order to keep the mass of the mixture for preparing the toughened PEEK film unchanged, the amount of PEEK resin is reduced accordingly. That is, the composition of the mixture is: 67 wt% PEEK resin, 15 wt% potassium titanate whiskers, 10 wt% zirconium phosphate and 8 wt% PTFE micro powder.
[0055] Molding quality verification: Ten bearing samples were continuously prepared using the same process parameters as described above. The toughened PEEK sliding layer and interface area after reverse rolling were inspected by macroscopic observation. No macroscopic cracks, wrinkles, or interlayer separation were observed in any of the ten samples, and the reverse rolling pass rate was 100%.
[0056] Performance test results: The toughened PEEK sliding layer has a tensile strength of 84 MPa, an elongation at break of 31%, an interfacial shear strength of 34 MPa, a dry friction coefficient of 0.13, and a wear rate of 5.0 × 10⁻⁶. -7 mm 3 / (N·m). Based on the test results, it is inferred that an excessively high proportion of zirconium phosphate is prone to agglomeration, which, as hard particles, becomes a source of defects at the interface, weakening the interfacial bonding strength (reducing the interfacial shear strength); at the same time, excessive agglomerates are more likely to peel off during friction, resulting in a decrease in the wear resistance of the material instead of an increase.
[0057] Example 8 This embodiment provides a method for preparing a self-lubricating bearing. The only difference between this method and Embodiment 1 is that in step 2), when preparing the toughened PEEK film, the mass percentage of the PTFE micro powder is adjusted from 8 wt% to 12 wt%. In order to keep the mass of the mixture for preparing the toughened PEEK film unchanged, the amount of PEEK resin is reduced accordingly. That is, the composition of the mixture is: 68 wt% PEEK resin, 15 wt% potassium titanate whiskers, 5 wt% zirconium phosphate and 12 wt% PTFE micro powder.
[0058] Molding quality verification: Ten bearing samples were continuously prepared using the same process parameters as described above. The toughened PEEK sliding layer and interface area after reverse rolling were inspected by macroscopic observation. No macroscopic cracks, wrinkles, or interlayer separation were observed in any of the ten samples, and the reverse rolling pass rate was 100%.
[0059] Performance test results: The toughened PEEK sliding layer has a tensile strength of 75 MPa, an elongation at break of 33%, an interfacial shear strength of 38 MPa, a dry friction coefficient of 0.12, and a wear rate of 4.8 × 10⁻⁶. -7 mm 3 / (N·m). Based on the test results, it is inferred that the excessive proportion of PTFE micro powder, although ensuring processing fluidity, severely weakens the continuous phase structure of PEEK resin due to the excessive small molecule lubricant, resulting in a significant decrease in the material's mechanical strength (tensile strength) and thus impairing its overall wear resistance.
[0060] Comparative Example 1 This comparative example provides a method for preparing a self-lubricating bearing. The only difference between this method and Example 1 is that the gradient copper powder layer has a homogeneous structure, uses a single particle size (median particle size 80 μm), and has the same total thickness as in Example 1. After sintering, a homogeneous copper powder layer with a porosity of 25% is formed.
[0061] Performance test results: 30% uncoiling pass rate (interfacial peeling occurred); interfacial shear strength 28 MPa. Based on the test results, it is inferred that the lack of a gradient structure leads to a significant decrease in bonding strength and a sharp increase in the risk of uncoiling cracking.
[0062] Comparative Example 2 This comparative example provides a method for preparing a self-lubricating bearing. The only difference from Example 1 is the sintering process of the porous copper powder buffer layer: the original method of "first heating to 700°C at a heating rate of 5°C / min and holding for 30 minutes to complete low-temperature pre-sintering; then rapidly heating to 880°C at a heating rate of 15°C / min and holding for 10 minutes for final sintering" is adjusted to "directly heating to 880°C at a heating rate of 5°C / min and holding for 40 minutes." All other process parameters are exactly the same as in Example 1. After this process adjustment, the porosity P1 of the dense copper powder transition layer was measured to be 16%, the porosity P2 of the porous copper powder buffer layer was 20%, the porosity difference P2-P1=4%, and the pore size distribution of the porous layer was 50~150μm.
[0063] Performance test results: PEEK melt penetration depth was only 30%; interfacial shear strength was 30 MPa; and the uncoiling pass rate was 80% (some samples showed cracking at weak points in the interfacial bonding). Based on the test results, it is inferred that insufficient porosity difference and excessively small pore size jointly led to insufficient PEEK melt penetration, preventing the formation of an effective interlocking structure.
[0064] Comparative Example 3 This comparative example provides a method for preparing a self-lubricating bearing. The only difference between this method and Example 1 is that a porous copper powder buffer layer is prepared using copper powder with a median particle size of 50 μm, so that the interconnected pores formed are mainly distributed in the range of 100~150 μm.
[0065] Performance test results: PEEK melt penetration depth was 40%; interfacial shear strength was 32 MPa; and the anti-rolling pass rate was 85%. Based on the test results, it is inferred that excessively small pore size severely hinders PEEK melt penetration, affecting industrialization efficiency and final bonding strength.
[0066] Comparative Example 4 This comparative example provides a method for preparing a self-lubricating bearing. The only difference between this method and Example 1 is that the cooling rate of the thermoplastic film formation is controlled at 5°C / s when preparing the toughened PEEK film.
[0067] Performance test results: PEEK crystallinity was 28%; elongation at break was 22%; and the roll-out pass rate was 60% (microcracks appeared in the toughened PEEK sliding layer). Based on the test results, it is inferred that the excessively slow cooling rate led to excessive crystallinity, reduced material ductility, and inability to meet the roll-out molding requirements.
[0068] Comparative Example 5 This comparative example provides a method for preparing a self-lubricating bearing. The only difference between this method and Example 1 is that the cooling rate of the thermoplastic film formation is controlled at 100°C / s when preparing the toughened PEEK film.
[0069] Performance test results: PEEK crystallinity is 18%; wear rate is 8×10⁻⁶. -7 mm 3 / (N·m); the unwinding pass rate was 100%. Based on the test results, it is inferred that the excessively fast cooling rate led to insufficient crystallinity. Although it did not affect the molding, the wear resistance of the material was significantly reduced.
[0070] Comparative Example 6 This comparative example provides a method for preparing a self-lubricating bearing, which differs from Example 1 only in that the composite material is heated to 130°C for plastic bending during the reverse rolling process.
[0071] Performance test results: 0% roll-out pass rate (brittle fracture occurred in the toughened PEEK sliding layer). Based on the test results, it is inferred that the excessively low temperature caused the material to be in a glassy state, lacking the ability to undergo plastic deformation.
[0072] Comparative Example 7 This comparative example provides a method for preparing a self-lubricating bearing, which differs from Example 1 only in that the composite sheet is heated to 190°C for plastic bending during the reverse rolling process.
[0073] Performance test results: 70% of the roll-out pass rate (the toughened PEEK sliding layer underwent excessive deformation and flow, resulting in loss of dimensional accuracy). Based on the test results, it is inferred that excessively high temperatures enhance the material's viscosity and flowability, leading to uncontrollable deformation under back pressure.
[0074] Comparative Example 8 This comparative example provides a method for preparing a self-lubricating bearing, which differs from Example 1 only in that no back pressure (0 MPa) is applied during the reverse rolling process.
[0075] Performance test results: 50% of the composite panels passed the anti-rolling test (obvious wrinkling and interlayer separation were observed at the bending points). Based on the test results, it is inferred that back pressure is crucial for suppressing instability of each layer during bending.
[0076] Comparative Example 9 This comparative example provides a method for preparing a self-lubricating bearing. The difference between this method and Example 1 is that it uses the same substrate support layer and gradient copper powder layer structure. The toughened PEEK sliding layer uses the same mixture as in Example 1 (75wt% PEEK resin, 15wt% potassium titanate whiskers, 5wt% zirconium phosphate, 5wt% PTFE micro powder), but is formed using a conventional injection molding process. The specific steps are as follows: the mixture is plasticized at 380°C using an injection molding machine, then injected into a mold at 180°C for molding. After holding pressure and cooling, a PEEK layer is obtained with a thickness of approximately 2.0 mm, which is comparable to the thickness of the toughened PEEK sliding layer in Example 1.
[0077] Performance test results: PEEK crystallinity 35%; elongation at break 25%; interfacial shear strength 21MPa; reverse rolling could not be performed, forced reverse rolling yield was 0%, wear rate: 3.0×10 -7 mm 3 / (N·m).
[0078] Based on the test results of the above embodiments and comparative examples, the elongation at break of Embodiments 1 to 8 of the present invention all reached over 24%, confirming that the material possesses excellent plastic deformation capacity; the interfacial shear strength of all embodiments reached over 33 MPa; in terms of molding performance, the pass rate of all embodiments in the reverse rolling molding verification was 100%. Among them, although Embodiments 4 (preheating step omitted), 6 (whisker ratio too high), 7 (zirconium phosphate ratio too high), and 8 (PTFE micro powder ratio too high) showed a certain degree of decline in other performance indicators, they were still significantly better than all comparative examples in terms of ductility, interfacial bonding strength, and reverse rolling molding performance. However, Comparative Examples 1 to 9 could not effectively solve the problems of insufficient ductility, low interfacial bonding strength, and easy cracking during reverse rolling of existing injection-molded PEEK bearings.
[0079] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A method for preparing a self-lubricating bearing, characterized in that, include: Preparation of a gradient copper powder layer: A dense copper powder transition layer and a porous copper powder buffer layer are deposited and sintered on a substrate support layer, wherein the dense copper powder transition layer is directly bonded to the substrate support layer, and the porous copper powder buffer layer is superimposed on the dense copper powder transition layer; wherein, the ratio of the median particle size of the copper powder used in the porous copper powder buffer layer to that used in the dense copper powder transition layer is ≥7.5:1; the difference between the porosity P2 of the porous copper powder buffer layer and the porosity P1 of the dense copper powder transition layer satisfies P2-P1≥25%; the porous copper powder buffer layer forms interconnected pores with a diameter of 200~500μm; Preparation of toughened PEEK film: A mixture containing PEEK resin, whiskers, solid lubricant and flow modifier is thermoplasticized into a film. The cooling rate of the thermoplastic film is 20~80℃ / s. Composite processing: The toughened PEEK film and the gradient copper powder layer are hot-pressed together to obtain a composite material containing a toughened PEEK sliding layer, a gradient copper powder layer and a substrate support layer from top to bottom. Reverse rolling forming: The composite sheet is heated to 150~170℃ for plastic bending and a back pressure of 0.5~2MPa is applied. Finally, it is rolled and welded to form a self-lubricating bearing. The sintering process of the dense copper powder transition layer includes: heating to 850℃~900℃ at a heating rate of 3~6℃ / min in a vacuum environment, and holding at that temperature for 30~90min to form a high-temperature sintering layer. The sintering process of the porous copper powder buffer layer includes: heating to 680℃~720℃ at a heating rate of 3~6℃ / min in a vacuum environment, holding for 20~60min for low-temperature pre-sintering, then heating to 850℃~900℃ at a heating rate of not less than 10℃ / min, holding for 5~20min for rapid sintering, and then rapidly cooling at a cooling rate of not less than 50℃ / s. The substrate support layer includes a low-carbon steel substrate; The hot-pressing composite process includes: covering a toughened PEEK film onto a gradient copper powder layer to form a composite system and then performing a hot-pressing process. The hot pressing process includes the following steps: a) Stepwise heating: First, heat the composite system from room temperature to 280-320℃ at a heating rate of 3-6℃ / min, hold for 5-15min for preheating and temperature equalization, and then continue heating to 380-400℃ at a heating rate of 3-6℃ / min to fully melt the toughened PEEK film. b) Segmented pressurization: During the melting stage, under vacuum conditions, first apply a pressure of 3~6MPa and maintain it for 3~8min; then increase the pressure to 12~18MPa and maintain it for 20~30min.
2. The method for preparing a self-lubricating bearing according to claim 1, characterized in that, The median particle size of the copper powder used in the dense copper powder transition layer is 15~25μm; And / or, the porosity P1 of the dense copper powder transition layer is 10~16%; And / or, the median particle size of the copper powder used in the porous copper powder buffer layer is 130~170μm; And / or, the porosity P2 of the porous copper powder buffer layer is 40~45%; And / or, the copper powder used in laying the dense copper powder transition layer and the porous copper powder buffer layer includes copper-tin alloy powder and / or copper-tin-zinc alloy powder.
3. The method for preparing a self-lubricating bearing according to claim 1 or 2, characterized in that, In the step of preparing the toughened PEEK film, the mixture contains 53-82 wt% PEEK resin, 10-25 wt% whiskers, 3-10 wt% solid lubricant and 5-12 wt% flow modifier, based on a mass of 100 wt%. And / or, the temperature for thermoplastic film formation is 375℃~395℃; And / or, the thermoplastic film formation method includes casting film formation and / or calendering film formation; And / or, the PEEK crystallinity in the toughened PEEK film is 20%~25%.
4. The method for preparing a self-lubricating bearing according to claim 1 or 2, characterized in that, The whiskers include at least one of potassium titanate whiskers, calcium sulfate whiskers, and silicon carbide whiskers; And / or, the aspect ratio of the whiskers is >10; And / or, the solid lubricant includes at least one of zirconium phosphate, molybdenum disulfide, and graphite; And / or, the flow modifier includes at least one of polytetrafluoroethylene micropowder, polyethylene wax, and stearate.
5. The method for preparing a self-lubricating bearing according to claim 1 or 2, characterized in that, The rolling welding method is high-frequency induction welding.
6. A self-lubricating bearing for a wind turbine gearbox, characterized in that, It is prepared by the method for preparing a self-lubricating bearing as described in any one of claims 1 to 5.
7. The self-lubricating bearing according to claim 6, characterized in that, The thickness of the substrate support layer is 8~10mm; And / or, the thickness of the dense copper powder transition layer is 0.05~0.1mm; And / or, the thickness of the porous copper powder buffer layer is 0.3~0.6mm; And / or, the thickness of the toughened PEEK sliding layer is ≥0.5mm.
8. A wind turbine generator set, characterized in that, The gearbox uses the wind turbine gearbox self-lubricating bearing as described in claim 6 or 7.
Citation Information
Patent Citations
High-performance copper-nickel-based powder metallurgy porous oil-containing bearing and production process thereof
CN103909271A
Sliding bearing and method of making a sliding bearing material
US6042778A
